Kajian Massa Jenis Bahan Bakar Minyak dari Pengolahan Sampah Plastik dengan Pirolisis - Isnaini Lilis Elviyanti; Syukron Ahmad Aftah; Titi Maemunah; Dwiyono Waluyo; M. Ngabdul Kafi (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Processing plastic waste into fuel oil with pyrolysis technology. Research on plastic oil as an alternative fuel has been widely conducted. One of them is research on processing plastic bag waste into fuel oil with pyrolysis technology. In this study, a set of pyrolysis equipment was made by Lecturers and Students of UMNU Kebumen. The plastic waste used in this study was 1 kg of plastic bag. Meanwhile, the pyrolysis process used a temperature of 250oC-300oC. The fuel oil produced in the pyrolysis process of this study was approximately 400 ml. The average density of fuel oil from plastic bag waste was 0.733 gr/ml. The results of this density calculation are in the possibility of the density of gasoline, namely 0.710 gr/ml to 0.770 gr/ml. This pyrolysis process shows great potential for converting plastic waste into an environmentally friendly alternative energy source. Furthermore, the efficiency of this pyrolysis technology can be improved by adjusting the temperature and processing time, as well as by selecting a wider variety of plastic types. This technology has the potential to be applied more widely in plastic waste management within the community as a solution to reduce environmental pollution while generating renewable energy.